Four-year effects of a 2-year nutrition- and gender-sensitive agricultural program on women’s nutritional status, knowledge, and empowerment in rural Burkina Faso - Bliznashka, Lilia; Becquey, Elodie; Ruel, Marie T.; Olney, Deanna K. (SAGE Publications, 2022)
Little is known about the sustained effects of nutrition- and gender-sensitive agricultural programs (NSAPs) after they end.To examine the 4-year effects (2010-2014) of a 2-year NSAP (2010-2012) on women’s outcomes in rural Burkina Faso.We used baseline (2010) and endline (2012) data from a cluster-randomized controlled trial of Helen Keller International’s Enhanced Homestead Food Production (EHFP) program and baseline (2014) data from a new program. We included 134 women: 82 who participated in the 2-year EHFP program (treatment) and 52 who did not (control). We examined program (2010-2012), post-program (2012-2014), and overall 4-year effects (2010-2014) using difference-in-difference analysis (DID).We found significant positive program effects (2010-2012) on women’s underweight prevalence (DID: 16.44 percentage points [pp]; P = .09) and on women’s knowledge about appropriate age to introduce liquids (DID: 28.40 pp; P = .01). Although there were no significant postprogram effects (2012-2014), differences found in 2012 between the treatment and control group were sustained resulting in an overall 4-year (2010-2014) reduction in women’s underweight prevalence (DID: 18.26 pp; P = .02) and an improvement in women’s knowledge about appropriate age to introduce liquids (DID: 31.29 pp; P = .02). We observed no postprogram or overall 4-year effects on women’s knowledge of child feeding and handwashing practices or women’s empowerment.Nutrition- and gender-sensitive agricultural programs demonstrate potential for sustained improvements in women’s nutritional status and nutritional knowledge. Postprogram assessments of NSAPs should be embedded in program evaluations to help further understand the potential of NSAPs to generate sustainable impacts on women’s outcomes.